A Case of Hypereosinophilia With Serositis Responsive to Mepolizumab - Emily Jezewski; Bryant R. England; Jill A. Poole; Cory Rohlfsen (Annals of Internal Medicine: Clinical Cases)
Idiopathic hypereosinophilic syndrome (IHES) is a disorder characterized by blood and tissue eosinophilia with eosinophil-driven tissue damage most commonly affecting the skin, lungs, and gastrointestinal tract and to a lesser degree the cardiovascular and coagulation systems. We discuss a case of IHES in a 62-year-old man who presented with serositis-predominant symptoms including ascites, pleural effusion, and an inflammatory polyarthritis with 6.0 × 109 eosinophils per liter with exclusion of other conditions to explain disease. This was a unique case of IHES with serositis at presentation without detectable autoimmune serologies and adds to the variability of a heterogeneous group of disorders with inadequately understood pathology.